(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This work highlights the primary effects of externalities on businesses, organizations, and teams. It then discusses the necessity for adapting and complementing traditional concepts, models, and theories of negotiation in this increasingly diverse and complex nonmarket arena. A third topic focuses on strategic negotiations with Governments, one of the most potent components among nonmarket forces. Finally, the work provides a list of practical recommendations for negotiators in the new era of externalities’ impacts and nonmarket prominence.